A second generation of carbamate-based fatty acid amide hydrolase inhibitors with improved activity in vivo - Clapper, Jason R. (2009)
The fatty acid ethanolamides are a class of signaling lipids that include agonists at cannabinoid and type-α peroxisome proliferator-activated receptors. In the brain, these compounds are primarily hydrolyzed by the intracellular serine enzyme fatty acid amide hydrolase (FAAH). O-aryl carbamate FAAH inhibitors such as URB597 are being evaluated clinically for the treatment of pain and anxiety, but interactions with carboxylesterases in liver might limit their usefulness. Here we explore two strategies aimed at overcoming this limitation. Lipophilic N-terminal substitutions, which enhance FAAH recognition, yield potent inhibitors but render such compounds both susceptible to attack by broad-spectrum hydrolases and inactive in vivo. By contrast, polar electron-donating O-aryl substituents, which decrease carbamate reactivity, yield compounds, such as URB694, that are highly potent FAAH inhibitors in vivo and less reactive with off-target carboxylesterases. The results suggest that an approach balancing inhibitor reactivity with target recognition produces FAAH inhibitors that display significantly improved drug-likeness.